Impact and acceptability of HIV self-testing for trans men and trans women: A mixed-methods subgroup analysis of the SELPHI randomised controlled trial and process evaluation in England and Wales. (February 2021) - Witzel, T. Charles; Wright, Talen; McCabe, Leanne; Gabriel, Michelle M.; Wolton, Aedan; Gafos, Mitzy; Ward, Denise; Lampe, Fiona C.; Phillips, Andrew N.; Trevelion, Roy; Collaco-Moraes, Yolanda; Harbottle, Justin; et al.
Abstract: Background: Globally, trans people are disproportionately affected by HIV, but research on strategies to increase testing are limited. SELPHI is a randomised-controlled-trial (RCT) of 10, 135 cis men, trans men, and trans women reporting lifetime anal intercourse with male partners ( cis or trans), evaluating whether the offer of free HIV self-testing (HIVST) increases diagnosis. This subgroup analysis from the SELPHI RCT aims to describe key HIVST outcomes and HIVST acceptability for trans people. Methods: SELPHI recruited using social networking and trans focused social media. Participants were randomised 60/40 to baseline HIVST (Biosure™) (BT) vs no baseline HIVST (nBT); and at 3-months (if completed the survey and reported recent CAI) 50/50 to 3-monthly HIVST (RT) vs no repeat HIVST (nRT). Outcomes were self-reported through online surveys. We conducted a qualitative study of semi-structured peer-led participant interviews ( n = 20) exploring HIVST motivations and experiences. These were analysed using a framework approach. Findings: SELPHI recruited and randomised 118 trans men and trans women (94 trans men, 24 trans women), of whom 20 (16 trans men, 4 trans women) underwent the second randomisation. Median age at baseline was 29 (IQR: 22, 37), 79% were white, 79% were UK born, 37% had degree level education, and 31% had never tested for HIV. 62% ( n = 59) of trans men completed the 3-month survey, but survey completion by trans women in nBT was too low (1/11) for randomised comparison. In trans men HIV testing uptake by 3 months was significantly higher in BT (95% 36/38) vs nBT (29%, 6/21) (RR=3.32 (1.68, 6.55) p <0.001). Trans people randomised to RT reported 3 times higher rate of HIV testing compared to nRT during the two-year follow-up (IRR 3.66 (1.86, 8.01) p <0.0001). STI testing frequency (mean number of tests during each 13 week period/ 2-year follow-up) was not significantly different across interventions: RT (0.03) and nRT (0.01) (IRR=1.86 95%CI; 0.77, 5.15; p = 0.15). Social harms were rare. Acceptability was very high in BT: 97% (38/39) found instructions easy to understand, 97% (37/38) found the HIVST simple to use and 100% (39/39) reported good overall experience. In interviews, reported HIVST benefits included increased autonomy, privacy, convenience and avoidance of health care providers perceived to be discriminatory and services that increased dysphoria. Minor lancet and test processing issues were reported. Interpretation: HIVST significantly increased testing uptake and frequency in trans men and trans people overall, although recruitment and retention of trans women was low. HIVST acceptability was high and indicates easy access to this novel technology may increase HIV testing access for this key population.